2006
DOI: 10.1121/1.2335420
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic characterization of human cancellous bone using the Biot theory: Inverse problem

Abstract: This paper concerns the ultrasonic characterization of human cancellous bone samples by solving the inverse problem using experimental transmitted signals. The ultrasonic propagation in cancellous bone is modeled using the Biot theory modified by the Johnson et al. model for viscous exchange between fluid and structure. The sensitivity of the Young modulus and the Poisson ratio of the skeletal frame is studied showing their effect on the fast and slow wave forms. The inverse problem is solved numerically by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…It has been found that the predictions are particularly sensitive to the assumed values of viscous characteristic length. The 'best-fit' characteristic length values for the two replicas cited in Table 1 are about 13 times those found for real bone which lie between 5 and 10 lm [3,5]. This is consistent with the physical scaling of the replicas.…”
Section: Theorysupporting
confidence: 73%
See 1 more Smart Citation
“…It has been found that the predictions are particularly sensitive to the assumed values of viscous characteristic length. The 'best-fit' characteristic length values for the two replicas cited in Table 1 are about 13 times those found for real bone which lie between 5 and 10 lm [3,5]. This is consistent with the physical scaling of the replicas.…”
Section: Theorysupporting
confidence: 73%
“…Cortical bone may generally be considered to be solid; cancellous bone consists of a complex open-celled porous network of rod-and plate-shaped elements termed trabeculae. In order to understand the dependence of ultrasound propagation, in particular, upon the material and structural properties of cancellous bone, Biot-based theories have been used extensively [1][2][3][4][5][6][7][8][9]. Biot theory predicts two compressional waves, often referred to as 'fast' and 'slow', when the waves propagating through the solid frame of bone and marrow are in-phase and out-of-phase respectively, and a shear wave.…”
Section: Introductionmentioning
confidence: 99%
“…It is diffusive at low frequencies and propagative at high frequencies. In this section, the direct and inverse scattering problems for the ultrasonic propagation in porous material having an elastic frame are solved [42][43][44][45][46]. An experimental application on human cancelous bone is discussed [42,43].…”
Section: Modified Biot Theorymentioning
confidence: 99%
“…The sensitivity of E b and ν b has been examined in Ref. [43] As an application of this model, some numerical simulations are compared with experimental results. Experiments are performed in water using two broadband Panametrics A 303S plane piezoelectric transducers with a central frequency of 1 MHz in water, and diameter of 1cm.…”
Section: Ultrasonic Characterization Of Human Cancellous Bone Using Tmentioning
confidence: 99%
“…Obtaining structural images of a porous material, and estimating its physical properties, is a topic of considerable interest in many branches of activities in geophysics, underwater acoustics, civil engineering, and biomechanics [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%